An Analysis of The Effect of Corporate Characteristics and Auditor Characteristics on Audit Fee - Evana, Einde; Farichah, Farichah; Mirfazli, Edwin; Idris, Agus Zahron; Tudor, Adriana Tiron (FEB - Universitas Lampung, 2019)
The title of this study is an analysis of the effect of corporate characteristics and auditor characteristics on the audit fee. The study aims to prove that the audit fee is influenced by the company characteristics (company size, business complexity, risk, profitability) and the manufacturing companies listed on the Stock Exchange in 2010-2014. The technique of sampling with purposive sampling obtains 88 companies, which is relevant to the multiple regression analysis tools. The results of this study indicate the significant effect among variables company size, the company profitability, and the auditor size toward the audit fee. However, the company’s complexity, the company’s risk, and audit tenure have no significant effect on the audit fee.